Reliability Assessment Models of System Under a Mixed Run Shock With Phase‐Type Distribution - Fan, Yiting; Tang, Jiayin (Quality and reliability engineering international, 2025)
In this article, the reliability assessment models of the dependent competing failure process (DCFP) of systems are established under mixed shocks, combining run shock and extreme shock. We explored two types of modes: the first type of reliability assessment model integrates a mixed shock process and a single degradation process. Established a soft failure reliability model based on degradation threshold assessment method, a hard failure model using a phase‐type distribution survival function is presented. Finally, it constructs the relationship between the shock process and the degradation process using conditional probability. The second type of assessment model is composed of a mixed shock process and multiple degradation paths. In this case, the copula functions were used to analyze the dependency between multiple degradation processes. Last, the effectiveness of the proposed models was demonstrated through two examples involving micro‐electro‐mechanical system devices and aircraft engine.